Respuesta :

Answer:

15

Step-by-step explanation:

Given the function

[tex]f(x)=5x+a[/tex]

and [tex]f^{-1} (10)=-1(f^{-1} \text{is the inverse function of f})[/tex]

let f(x)=y

Substitute in f(x)

[tex]y=5x+a\\y-a=5x\\x=\frac{y-a}{5}[/tex]

From the definition inverse function

if [tex]f(x)=y [/tex]    ⇒   [tex]f^{-1} (y)=x[/tex]

Substitute this in the above expression

[tex]f^{-1} (y)=\frac{y-a}{5}[/tex]

Substitute y=10

[tex]f^{-1} (10)=\frac{10-a}{5}\\-1=\frac{10-a}{5}\\-5=10-a\\a=10+5\\a=15[/tex]

Therefore a=15

Otras preguntas